The political problem of religious pluralism: and why philosophers can't solve it - Kozinski, Thaddeus J. (Lexington Books, 2010)
Rawls's postmodern turn -- The failure of the overlapping consensus -- Overlapping consensus in a new Christendom -- Maritain's democratic faith : a sign of contradiction -- MacIntyre's tradition constituted rationality -- A critique of MacIntyre : why philosophy isn't enough